Causes of mortalities of King penguins in a recently established colony in Southern Chile - Godoy Reyes, Claudia; Munoz, Luis; Garcia Borboroglu, Jorge Pablo
King penguin breed on sub-Antarctic islands between latitude 45oS and 55oS. In 2010, a new colony was established at Bahía Inútil, Tierra del Fuego, Chile. The king has the longest annual cycle of any of the penguins, taking fourteen months to rear one chick. Breeding success was extremely low, with complete breeding failures for many years. Our goal was to assess the causes of chick death from 2014 to 2018. We performed post mortem examination and classified the external macroscopic signs as non-infectious (starvation, predation or unknown) or infectious. We performed necropsies on 80% of all dead chicks, registering age and morphological measures and conducting viral and histopathological analysis. In four years, most chicks died before 3 months-old due to outbreaks of infectious diseases. However, this pattern was not consistent among all years, since in 2017 most chicks (55%) died older than 5 months old and predated by grey foxes, an introduced species.The main macroscopic signs were hepatomegaly and enteritis, but it was not possible in all of the cases to precise the principal infectious agent. Infectious disease is one of the main causes of mortality in wild animals worldwide. Few studies have monitored studies on infectious signs on wild penguin populations, and this is the first one on king penguins. Our study is the starting point of a long-term health surveillance program, which is essential to detect emergent pathogens. Fil: Godoy Reyes, Claudia. Global Penguin Society; Estados Unidos Fil: Munoz, Luis. Global Penguin Society; Estados Unidos. Parque Pingüino Rey, Tierra del Fuego; Chile Fil: Garcia Borboroglu, Jorge Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina. Global Penguin Society; Estados Unidos 10th International Penguin Congress Dunedin Nueva Zelanda University of Otago